Предмет: Математика, автор: nastyanoskova07

ДПомогите пожалуйста! Срочно!!!
1.-3*(9х-15)+6х= При х=-1
2.2*(4х-1)-8х+3= При х=-2
3.-4*(8х+1)-9= При х=-3
4.6*(8х-4)-5х+4
Срочно пж!

Ответы

Автор ответа: shpurko
0

Пошаговое объяснение:

1)

 - 3 \times (9x - 15) + 6x

 - 27x + 45 + 6x =  \\  =    - 21x + 45 \\ x =  - 1 \\  \\  - 21 \times ( - 1) + 45 = 21 + 45 = 66

2)

2(4x - 1) - 8x + 3 \\

8x - 2 - 8x + 3 =  - 2 + 3 = 1 \\  \\ x = 2

3)

 - 4(8x + 1) - 9

 - 32x - 4 - 9 =  - 32 - 13 \\  \\ x =  - 3 \\  \\  - 32 \times ( - 3) - 13 = 96 - 13 = 83

4)

6(8x - 4) - 5x  + 4

48x - 24 - 5x + 4 = 43x - 20

Похожие вопросы